2012
DOI: 10.1590/s1519-69842012000100012
|View full text |Cite
|
Sign up to set email alerts
|

Changes in phytoplankton composition in response to tides, wind-induced mixing conditions, and freshwater outflows in an urbanised estuarine complex

Abstract: Recent reports have shown an increase in potentially harmful phytoplankton in Santos bay (Southeastern Brazilian Coast), located in a highly urbanised estuarine complex. Prediction of blooms is, thus, essential but the phytoplankton community structure in very dynamic regions is difficult to determine. In the present work, we discriminate bloom forming microphytoplankton dominance and their relationship to physical and meteorological variables to look for patterns observed in different tides and seasons. Compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
6

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 43 publications
1
14
0
6
Order By: Relevance
“…Local CDOM produced by the degradation of algal estuarine species, and bacteria consumption will likely modify the characteristics of CDOM. Very high a cdom (443) was observed during the neap tide survey in September 2007, probably reflecting the susceptibility of the Santos Bay to periodic external contributions of CDOM (Moser et al, 2012). One possible source of this anomalous increase in CDOM could be freshwater released from the Henry Borden hydroelectric power plant (Gasparro et al, 2008) located in the city of Cubatão, 14 km uphill from Santos.…”
Section: Time Variability Of Optical Parametersmentioning
confidence: 99%
See 2 more Smart Citations
“…Local CDOM produced by the degradation of algal estuarine species, and bacteria consumption will likely modify the characteristics of CDOM. Very high a cdom (443) was observed during the neap tide survey in September 2007, probably reflecting the susceptibility of the Santos Bay to periodic external contributions of CDOM (Moser et al, 2012). One possible source of this anomalous increase in CDOM could be freshwater released from the Henry Borden hydroelectric power plant (Gasparro et al, 2008) located in the city of Cubatão, 14 km uphill from Santos.…”
Section: Time Variability Of Optical Parametersmentioning
confidence: 99%
“…The resuspension of bottom sediments can occur episodically during strong tidal currents (Alfredini et al, 2008). Surveys have shown high ammonium, phosphate and chlorophyll concentrations in the Santos estuarine complex year round (Gianesella et al, 2000;Aguiar and Braga, 2007), and changes in the phytoplankton species composition and size structure (mainly diatoms, dinoflagellates and mixotrophic dinofalgellates) have been related to freshwater input, tides and wave action (Moser et al, 2012).…”
Section: Study Areamentioning
confidence: 99%
See 1 more Smart Citation
“…It was proposed that S. cf. costatum should be considered an indicator of the influence of riverine waters on estuarine systems (MOSER et al, 2012). In the light of this scene, we here evaluate how phytoplankton composition responds to nutrient over-enrichment in a well-preserved sub-tropical estuary by means of controlled bioassays using the natural community of the Cananéia-Iguape Estuarine-Lagoon System and submitting the microalgae to different levels of eutrophication.…”
Section: Notes / Notasmentioning
confidence: 99%
“…costatum and Asterionellopsis glacialis (MOSER et al, 2012;VILLAC et al, 2008). Moser et al (2012) reviewed the dynamics of the phytoplankton in Santos bay and concluded that changes in microphytoplankton communities occur mainly in response to episodic changes in wind speed and direction and tides, but the results presented also give evidence of alterations in the temporal patterns of [Chl] and phytoplankton species composition during recent blooms. Despite the economic and ecological importance of the Santos estuarine complex, there is little systematic observation on phytoplankton dynamics available to date.…”
Section: Introductionmentioning
confidence: 99%